MA’BUNGA’ LALANG: THE AGRICULTURAL TRADITION OF LUWU SOCIETY - Thayyib, Magfirah (Kementerian Pendidikan dan Kebudayaan, 2021)
Every tradition has its own characteristics and wisdom values that make it worth to be studied and documented. This research aims to describe the tradition of ma’bunga’ lalang in the agricultural activities of Luwu society. The locus of this research was Luwu Regency, South Sulawesi Province. The data were obtained through observation on the practices/rituals in ma’bunga’ lalang tradition and interview the informants. The data were then transcribed, triangulated, presented descriptively, and connected to the relevant references. There are nine kinds of practices/ritual in ma’bunga’ lalang tradition following the stages of rice farming activities of Luwu society. Each practice/ritual has particular details of verbal and non-verbal acts which either performed by a bunga’ lalang (the leader of the tradition) himself representing the farmers in the village or performed together with all the farmers-villagers. Nowadays, ma’bunga’ lalang tradition is rarely performed due to several factors. Thus, it needs to be raised in the socio-cultural or local-governmental forum to raise the society awareness of the tradition and to discuss the preservation of the parts of the tradition that not contradict to religion and modern practice/science.